School Readiness in Implementing Kurikulum Merdeka: A Case Study in SMAN 15 Bandar Lampung - Fitriyani; Yanuar Dwi Prastyo (PT. Inovasi Teknologi Komputer, 2024)
The research investigates the readiness of SMAN 15 Bandar Lampung in implementing the